Sustainable Development Strategies For Madurai: Urban Challenges And Preserving The Environment (Journal of Namibian Studies : History Politics Culture, 2023)
This abstract outlines sustainable development strategies tailored for Madurai, aiming to confront urban challenges while safeguarding the environment. The focus is on devising comprehensive approaches that align with the unique context of Madurai, considering its cultural and historical significance. The strategies encompass urban planning, resource management, and community engagement to foster a balanced and resilient urban environment. Emphasis is placed on integrating innovative technologies, promoting green infrastructure, and enhancing community awareness to achieve sustainable urban development in Madurai.